STRESS-LIMITING ANESTHESIA IN OPHTHALMOSURGERY (World Science, 2021)
Despite the significant advances made by modern anesthesiology in the perioperative management of patients, surgical interventions are still accompanied by a high proportion of complications and even deaths. At the same time, it is known that in 50% of cases mortality and serious postoperative complications could be prevented. After performing a thorough study of the factors affecting the increase in hospitalization and postoperative recovery (Kehlet H., 1997; Kehlet H., Wilmore D., 2002), it was determined that the surgical stress response is the most significant inducer of dysfunction of various organs. and systems. To date, it has been established that general anesthesia in its classical sense does not allow achieving complete protection of the patient from surgical trauma. More complete protection can be achieved by combining general anesthesia with regional blockages and adjuvant drugs with stress-protective properties. In the present study, we compared the severity of the surgical stress response and pain syndrome in patients operated on under conditions of multicomponent balanced general anesthesia (group K) with patients who received a stress-limiting anesthesia regimen (group DB). In both groups, multicomponent anesthesia was performed, in group K, sibazone was used for sedation, in group DB, dexmedetomidine was used. Also, patients of the DB group underwent regional blockade (blockade of the pterygo-palatine fossa) before surgery. The main criteria for evaluating the results were: hemodynamic stability, blood glucose, the level of venous blood leukocytes and the severity of pain according to the VAS in the postoperative period. Both schemes made it possible to avoid pronounced fluctuations in hemodynamic and gas exchange parameters at all stages of the study. When analyzing blood glucose and leukocyte counts, it was found that patients in the control group had a more significant deviation of both indicators from the preoperative level than in the stress-limiting anesthesia group. In the study of pain syndrome, it was determined that in the control group the level of pain according to the VAS was higher at all stages of the study compared to patients in the group of stress-limiting anesthesia.